2018
DOI: 10.1038/s41598-018-19331-z
|View full text |Cite
|
Sign up to set email alerts
|

Extractable pool of biochar controls on crop productivity rather than greenhouse gas emission from a rice paddy under rice-wheat rotation

Abstract: The role of extractable pool of biochar in crop productivity and soil greenhouse gas (GHGs) emission is not yet clear. In this study, two biochars with and without extraction was added to a paddy before rice transplantation at 20 t·ha−1. Crop yield, plant traits and greenhouse gas emission monitored throughout a rice-wheat rotation. Between the biochar treatments, changes in bulk density and microbial biomass carbon were insignificant. However, the increase in organic carbon was similar between maize and wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Higher K content values were recorded for TB2 + CF showing increases by 54.1% in grains, of 42.9% in shoots and of 49.7% in roots over the CK group (Figure 3G–I). Our results are consistent with previous studies which reported that plant N, P and K contents improved with the co-application of biochar and chemical fertilizer application under pot and field conditions [5,31,44,45,46]. In present study, TB + CF amendments clearly affected N, P and K contents in grains, shoots and roots of wheat as compared to BB + CF, OB + CF and CF alone.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Higher K content values were recorded for TB2 + CF showing increases by 54.1% in grains, of 42.9% in shoots and of 49.7% in roots over the CK group (Figure 3G–I). Our results are consistent with previous studies which reported that plant N, P and K contents improved with the co-application of biochar and chemical fertilizer application under pot and field conditions [5,31,44,45,46]. In present study, TB + CF amendments clearly affected N, P and K contents in grains, shoots and roots of wheat as compared to BB + CF, OB + CF and CF alone.…”
Section: Resultssupporting
confidence: 93%
“…Nutrients contents are dependent on the biochar pyrolysis temperature, time and feedstock [2,17,26]. Many studies have reported inconsistent results for crop yield, plant nutrients uptake [1,30,31] and soil properties [10,26]. These variations could be dependent on soil and biochar feedstock properties [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heightened global interests—especially in the field of agriculture research—have focused on the biochar, which is derived from biomass by artificial pyrolysis, and its potential to help mitigate global warming, improve crop productivity, and absorb heavy metals [ 7 ]. Some studies have found that biochar has the potential to reduce the decomposition of soil organic matter to counteract the release of CO 2 [ 8 ], increase grain yield, and improve water utilization efficiency [ 9 , 10 ]. The chemical stability of biochar has a carbon sequestration effect, which slows down the greenhouse effect and, thus, can be used as one of the CO 2 emission reduction measures in farmlands [ 11 ].…”
Section: Introductionmentioning
confidence: 99%